(untitled) (Journal of Mathematics Mechanics and Computer Science, 2018)
Theoretical research of effect of stoichiometry’s propane-oxygen mixture on the rate of production of hydrocarbon oxides. Mechanisms were selected such as GRI-3.0 Mechanism, n-Butane / oxygen / argon Mechanism, Saudi Aramco 1.3 Mechanism for developing the kinetic mechanism in combustion of wealthy mixtures propane - oxygen. Experimental data were taken from [3] and have been compared with the results of calculations by means of the aforementioned mechanisms. Among these three mechanisms were close to the data to experimental data that have been obtained with the use of GRI-3.0. Was developed by the reduced mechanism to describe the combustion propane in wealthy mixtures at high pressures. Obtained after the reduction kinetic mechanism (hereinafter - Skeletal mechanism) consists of 33 substances and 138 reactions (9 of them irreversible and 129 are reversible). Skeletal mechanism describes the kinetics of combustion a propane and formation of polluting substances at temperatures of 1200-2000 K, a stoichiometric ratio of propane / oxygen (phi = 2) and a pressure of 8 bar. A model testing was conducted on of the experimental data on the ignition delay time, the conversion of propane at high temperature oxidation, change component concentrations. Testing the model is fulfilled for the initial mixture temperature 1200-2000K, for the pressure p_0 = 8 bar and a stoichiometric fuel / oxygen φ = 2.